2014
DOI: 10.7860/jcdr/2014/7013.4011
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Autoimmune Polyglandular Syndrome (APS) in Patients with Type1 Diabetes Mellitus Followed up at A Teritiary Care Hospital

Abstract: The commonest autoimmune disorder associated with T1DM found in our study was AITD. Because genetic/ autoantibodies testing is not a feasible option, it is important to screen them with best available laboratory facilities and clinical assessment in view of high prevalence of associated autoimmune conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…The frequency of occurrence of these diseases is increased in children and adolescents with T1DM in comparison to healthy children [ 20 , 21 ]. These diseases are associated with the presence of specific autoantibodies in blood serum, which can be detected prior to the development of clinically overt disease [ 20 – 22 ]. There are ongoing investigations of the genetic basis of the coincidence of T1DM and other autoimmune diseases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency of occurrence of these diseases is increased in children and adolescents with T1DM in comparison to healthy children [ 20 , 21 ]. These diseases are associated with the presence of specific autoantibodies in blood serum, which can be detected prior to the development of clinically overt disease [ 20 – 22 ]. There are ongoing investigations of the genetic basis of the coincidence of T1DM and other autoimmune diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The results are described in Table 1 [ 23 ]. The occurrence of other autoimmune diseases in patients with type 1 diabetes deteriorates the quality of life and increases morbidity and mortality [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The coexistence of and relationship between TD and DM have been addressed by many researchers (Wu, 2000;Betterle and Zanchetta, 2003;Betterle et al, 2004;Barker et al, 2005;Blois et al, 2010;Hage et al, 2011;Shaikh et al, 2014). The effects of these concurrent conditions on different systems of the body have been discussed only as retrospective studies on the basis of some naturally occurring clinical case records in humans, but the data were found lacking in the context of research trials into such a syndrome and its effects on reproductive health.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of hypothyroidism on increasing insulin resistance and glucose metabolism is well documented 17 as thyroid hormones stimulate glucose uptake into peripheral tissues and enhance the effect of insulin action on glucose transport in to cell. 4,17 In hypothyroid patients this mechanism is disrupted leading to higher glucose levels leading to various acute and chronic complications of diabetes. 5 The strength of our study is the proper documentation of a large number of T1D subjects, however limitation of our study is that this is a single center study and antibody status was not checked in every subject due to financial constraints.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, genetic factors have also been postulated to be involved in the development of T1D and studies have shown that the development of T1D also increases the risk of development of other autoimmune diseases. The most frequent comorbid conditions in T1D include auto immune thyroid diseases [4][5][6][7][8] cardiac diseases (4-9%) pernicious anemia (5-10%), Addison's' disease (0.5%) and vitiligo (2-10%). 4,5 https://doi.org/10.1016/j.cegh.2019.01.001 Received 9 May 2018; Received in revised form 27 November 2018; Accepted 1 January 2019 Autoimmune thyroid diseases (ATD) are the most common autoimmune manifestations in children and adolescents with T1D 6,7 .…”
Section: Introductionmentioning
confidence: 99%